Impact of Carbon Tax and Financial Performance on Business Sustainability Transport Firms - Resha Mulyono; Abdhul Muadzin Hidayatulloh; Indra Lukmana Putra (Management Study Program, Faculty of Economics, Merdeka University Pasuruan. East Java. Indonesia, 2026)
abstrack Climate change has become a major global issue affecting environmental sustainability, economic stability, and business activities across various sectors, including transportation. The transportation sector is recognized as one of the largest contributors to carbon emissions due to its heavy reliance on fossil fuels. In response to environmental challenges, the Indonesian government implemented a carbon tax policy in 2022 as part of its sustainable fiscal reform agenda. The implementation of carbon tax is expected to encourage companies to reduce emissions and improve operational efficiency; however, it may also increase operational costs and affect corporate financial performance and sustainability.This study aims to analyze the effect of carbon tax and financial performance on the business continuity of transportation companies in Indonesia during the period 2022–2024. The background problem of this study is the limited empirical evidence regarding how environmental fiscal policies influence corporate sustainability, particularly in Indonesia’s transportation sector. The novelty of this study lies in its integration of carbon tax policy, financial performance, and business continuity within a single empirical framework focusing on transportation companies in Indonesia.This study employs a quantitative research approach using secondary data obtained from annual financial reports of transportation companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. Financial performance is measured using Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER). The collected data are analyzed using multiple regression analysis to examine the relationship between carbon tax and financial performance variables on business continuity.The findings indicate that financial performance significantly influences business continuity. Companies with strong profitability and liquidity tend to demonstrate better operational sustainability and adaptability to environmental regulations. Meanwhile, carbon tax policy creates additional operational pressures that may affect companies with weak financial conditions. The study concludes that transportation companies need to improve financial resilience and operational efficiency to maintain long-term sustainability under environmental regulatory pressures. The results of this study are expected to provide practical implications for policymakers and business practitioners in developing adaptive and sustainable business strategies. Abstrak Perubahan iklim isu global utama memengaruhi keberlanjutan lingkungan, stabilitas ekonomi, dan aktivitas bisnis di berbagai sektor, termasuk sektor transportasi. Sektor transportasi merupakan salah satu penyumbang emisi karbon terbesar karena ketergantungannya yang tinggi terhadap bahan bakar fosil. Sebagai respons terhadap tantangan lingkungan tersebut, Pemerintah Indonesia mulai menerapkan kebijakan pajak karbon pada tahun 2022 sebagai bagian dari agenda reformasi fiskal berkelanjutan. Implementasi pajak karbon diharapkan mampu mendorong perusahaan untuk mengurangi emisi karbon dan meningkatkan efisiensi operasional. Namun demikian, kebijakan ini juga berpotensi meningkatkan biaya operasional sehingga dapat memengaruhi kinerja keuangan serta keberlanjutan usaha perusahaan. Tujuan riset menganalisis pengaruh pajak karbon dan kinerja keuangan terhadap keberlangsungan usaha perusahaan transportasi di Indonesia selama periode 2022–2024. Permasalahan melatarbelakangi terbatasnya bukti empiris mengenai pengaruh kebijakan fiskal berbasis lingkungan terhadap keberlanjutan perusahaan, khususnya pada sektor transportasi di Indonesia. Kebaruan penelitian pada integrasi kebijakan pajak karbon, kinerja keuangan, dan keberlangsungan usaha dalam satu kerangka empiris yang berfokus pada perusahaan transportasi di Indonesia. Kajian kuantitatif data sekunder yang diperoleh dari laporan keuangan tahunan perusahaan transportasi yang terdaftar di Bursa Efek Indonesia (BEI) selama periode 2022–2024. Kinerja keuangan diukur menggunakan indikator Return on Equity (ROE), Current Ratio (CR), dan Debt to Equity Ratio (DER). Data dianalisis regresi linier berganda untuk menguji pengaruh pajak karbon dan kinerja keuangan terhadap keberlangsungan usaha. Hasil kinerja keuangan berpengaruh signifikan terhadap keberlangsungan usaha. Tingkat profitabilitas dan likuiditas yang baik cenderung memiliki keberlanjutan operasional yang lebih tinggi serta kemampuan adaptasi lebih baik terhadap regulasi lingkungan. Kebijakan pajak karbon menimbulkan tekanan biaya operasional tambahan yang berpotensi memengaruhi perusahaan dengan kondisi keuangan yang relatif lemah. Perusahaan transportasi memperkuat ketahanan keuangan, meningkatkan efisiensi operasional, serta mengembangkan strategi bisnis adaptif demi keberlanjutan usaha di tengah meningkatnya tekanan regulasi lingkungan. Temuan implikasi praktis bagi pembuat kebijakan dan pelaku usaha dalam merumuskan strategi bisnis yang berkelanjutan serta mendukung implementasi kebijakan fiskal hijau di Indonesia.